Contributions of attachment theory to clinical developmental practice - Tereno, Susana (2017)
Variations in the quality of attachment represent initiation conditions that, in the context of interaction between biological and environmental factors, play a dynamic role in the bio-psycho-social functioning of the individual. This article presents a literature review of the theory and investigation of attachment in childhood and aims to contribute to a developmental perspective in the practice of clinical practice. Binding research has clarified the effects on children of early experiences associated with: a) out-of-home care routines (eg nursery schools); b) separations (e.g., hospitalizations); c) significant disruption of care (eg adoption and foster families); d) the characteristics of children with special needs. In this developmental perspective, the question of the disorders of the bonding relationships, as well as the specificities of this type of relationship in children with certain pathologies is discussed. Clinical guidelines are presented for clinicians since relational aspects are central to the development of children and consequently to intervention.